Dominance and Leadership in the Equine Social Structure: A Preliminary Study About Mules and Sex Influence - Narciso, Matheus H.P.M. [UNESP]; da Luz, Marina P.F. [UNESP]; Maia, Caroline M.; Filho, José Nicolau P.P. [UNESP] (Elsevier, 2021)
Little is known about the dominance and leadership behaviors in the social structure of mules (Equus caballus × Equus asinus). Based on the frequency of threat and aggressive behaviors, we compared the social structure, dominance, and leadership of independent groups of mules and horses (n = 11 per group), and filmed the frequency of these behaviors over a period of four days. In both groups, aggressions were uncommon and, when based on threats, the social structure was linear and consistent with males ranking higher in dominance. When compared to horses, mules exhibited some agonistic social interactions without a recognized submissive individual and displayed more specific aggressive behaviors, whereas horses presented more specific threat behaviors. Comparing between groups, mares exhibited more leader behaviors than female mules, in contrast to male horses which showed fewer leader behaviors than male mules. Regarding behaviors within the mule group, males showed more leader and threat behaviors than females, while females showed more frequent aggression. While in horses, the females showed more leader behaviors than male horses and, although there were differences in specific agonistic behaviors, both sexes presented more often threat behaviors. In this preliminary study, we conclude that the social structure of mules, although similar to those of horses, showed to be less stable, since it involves more aggression and agonistic social interactions without a submissive. Moreover, although mules did not present a sex influence on leadership as horses did, they presented it on aggression: females showed more aggression than males.
Keywords: Behavior; Dominance; Hierarchy; Leadership; Mules